Left Atrial Low-Voltage Extent Predicts the Recurrence of Supraventricular Arrhythmias - Yannick Teumer; Luca Gold; Lyuboslav Katov; Carlo Bothner; Wolfgang Rottbauer; Karolina Weinmann-Emhardt (Journal of Cardiovascular Development and Disease)
The incidence of left atrial (LA) supraventricular arrhythmias is increasing. Even after LA ablation, recurrence of these tachycardias is common. MRI studies show that LA cardiomyopathy is a significant risk factor for recurrence and correlates with low voltage areas detected via 3D electroanatomic mapping (EAM). There are limited data on the impact of low voltage extent detected by EAM on recurrence-free survival. Voltage thresholds defining low voltage vary across different studies. This study aims to investigate the impact of the extent of low voltage areas in the LA on recurrence-free survival and to assess whether defining low voltage areas using thresholds of 0.5, 0.4, or 0.3 mV offers better predictive performance. Patients with atrial arrhythmia who underwent LA EAM at Ulm University Heart Center between September 2018 and September 2022 were included from the ATRIUM registry. ROC analysis determined the voltage threshold for predicting recurrence-free survival. Kaplan–Meier and logistic regression models adjusted for patient variables were used to analyze recurrence-free survival. Of 1089 screened patients, 108 met the inclusion criteria. ROC analysis indicated that a 0.4 mV threshold for low voltage provided the best predictive performance. Logistic regression showed a 1.039-fold increase in recurrence risk per percent increase in LA low voltage area (odds ratio = 1.039, 95% CI 1.014–1.064). Low voltage extent in EAM correlates with 1-year recurrence rate after ablation of left atrial supraventricular arrhythmias. The threshold of 0.4 mV is the most suitable for predicting recurrences of those examined.